Analisis Risiko Finansial Perbankan Melalui Artificial Intelligence (AI): Politik Hukum dan Potensi Pengembangan Hukum - Agustianto, Agustianto; Budi, Henry Soelistyo; Sudirman, Lu; Nurlaily, Nurlaily; Afdal, Windi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2025)
he integration of artificial intelligence (AI) into various sectors, including banking, has grown increasingly prevalent. AI holds significant potential in the banking system, particularly in financial risk analysis. However, its utilization requires a robust legal framework to ensure ethical and accountable application. This study aims to analyze the direction of Indonesia's legal policy and develop a legal framework model that supports the ethical use of AI for financial risk analysis in the banking sector. The research employs a normative legal research method. Through this method, the study identifies several normative issues that may negatively impact the use of AI for financial risk analysis. These issues range from fundamental legal norms, such as accountability for AI utilization, to more technical concerns, including transparency, cybersecurity, and data privacy. The findings highlight gaps in the current regulatory framework, necessitating an urgent response to accommodate the complexities introduced by AI technologies in financial systems. This research proposes a legal framework development model to provide a normative construction for relevant regulations. The proposed model emphasizes the pivotal role of the Financial Services Authority (OJK) in implementing and monitoring regulations based on the framework. By addressing these regulatory challenges, the model seeks to facilitate the ethical and responsible deployment of AI in financial risk analysis while safeguarding stakeholder interests and ensuring compliance with prevailing legal principles. Pemanfaatan artificial intelligence (AI) dewasa ini semakin terintegrasi ke dalam berbagai sektor, seperti salah satunya sektor perbankan. AI memiliki potensi yang signifikan dalam sistem perbankan, khususnya untuk digunakan dalam analisis risiko finansial. Namun pemanfaatan ini perlu diakomodasi dengan kerangka hukum yang memadai, untuk memastikan pemanfaatan sistem AI yang etis dan bertanggung jawab. Tujuan penelitian ini adalah untuk menganalisis arah politik hukum Indonesia serta mengembangkan model pengembangan hukum yang dapat diterapkan untuk mendukung pemanfaatan AI yang etis untuk tujuan analisis risiko finansial dalam sistem perbankan. Metode penelitian yang digunakan adalah metode penelitian hukum normatif. Dengan menggunakan metode penelitian hukum normatif, hasil penelitian ini menemukan beberapa permasalahan normatif yang dapat berdampak negatif terhadap pemanfaatan AI untuk analisis risiko finansial, mulai dari norma hukum yang mendasar seperti pertanggungjawaban mengenai pemanfaatan AI, hingga yang bersifat lebih teknis seperti transparansi, keamanan siber, dan privasi data. Penelitian ini mengusulkan model pengembangan hukum yang dapat dimanfaatkan untuk memberikan gambaran konstruksi normatif bagi beberapa peraturan perundang-undangan relevan, dengan mendukung OJK sebagai bagian sentral dari penerapan dan pengawalan regulasi berdasarkan model tersebut.